ANALISIS PERHITUNGAN HARGA POKOK PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE FIFO DAN AVERAGE DALAM MENENTUKAN HARGA POKOK PESANAN TEH MEREK TONG TJI PADA PT SEDAP HARUM AN ANALYSIS CALCULATION OF COST OF RAW MATERIAL INVENTORY USING FIFO AND AVERAGE IN ORDER TO DETERMINE THE COST OF TEA BRAND TONG TJI IN PT SEDAP HARUM - Widyastuti, Widyastuti; Afif, Muhammad Nur (Fakultas Ekonomi Universitas Djuanda, 2015)
This study aims to get the value of goods made by the company in determining the cost of the order tea brand Tong Tji at PT. Sedap Harum with a method LIFO, FIFO, and AVERAGE. Data analysis method used is by way of comparative descriptive describe and compare the results of calculations performed between LIFO, FIFO and AVERAGE. The results showed the results of the analysis of the calculation of the order cost brand Tong Tji using LIFO, FIFO, and AVERAGE shows there is a difference. The value of the results of calculation of the cost per kg of products is based on the LIFO method amounted to 23 237, 22 977 and the FIFO method of AVERAGE method amounted to 23 023. The calculation results indicate that the LIFO method produces estimates of high production costs so that the gross profit of the company that received low. While the value of the FIFO method and AVERAGE generate estimated production costs low with high gross profit.Keywords: Stock Price, Frequency and Bid-ask spreads